Islamism and democratization in Indonesia post-reformation era: socio-political analysis - Syahrir Karim,; Samsu Adabi Mamat,; Bayu Taufiq Possumah, (Universiti Kebangsaan Malaysia, 2014)
In general, this paper will explore features and patterns of Islamism in Indonesia after the downfall of Suharto’s regime in which people called it as reformation era. In Indonesian context, the Islamism at least have four characteristics; (i) promoting Islam as a sole basis in transforming society, (ii) acknowledging Islam as an ideology, (iii) among at the establishment of Islamic state, (iv) which is characterised by implementing Shari`ah laws in daily lives. These four attributes may be used in capturing the growth of Muslim’s perception on state and democracy in the era of Islamic revival. The above views spread in the various streams or any schools existed in Indonesia, both Islamic movements and other form that is very influential in the process of democracy in Indonesia.